Performance of Fifteen F5 Pedigree Upland Rice Lines in Ultisol - Luwih, Bagus Edi; Rustikawati, Rustikawati; Hindarto, Kanang Setyo (Akta Agrosia, 2017)
ABSTRACTRice (Oryza sativa L.) is a rice-producing crop that is the main food source for most of Indonesia's population. Although rice production increases but needs to be maintained. One of the efforts in maintaining rice production is by assembling superior paddy varieties that are adaptive to Ultisol soil. This study aims to compare the appearance of 15 lines of upland rice grown in Ultisol soil and choose the best lines based on index selection. The research was conducted on August 2015 until January 2016 at New Field Experiment Garden of Agriculture Faculty of Bengkulu University of Kandang Limun Sub-District, Muara Bangkahulu Sub-district, Bengkulu City. The experimental design was Randomized Block Design (RAKL) with 3 replications. As the treatment is 15 lines of rice are G1, G2, G3, G5, G8, G13, G16, G24, G30, G32, G35, G40, G44, G45, and G50. Of the 15 gogo rice strains tested showed that the generative and vegetative variables did not significantly affect the number of leaves, the number of productive tillers, the number of pithy grains per panicle, the weight of the grain per panicle, the weight of 100 grains, and the weight of grain per hill.keywords: upland rice, Ultisol, yield